2021
DOI: 10.3389/fphot.2021.700737
|View full text |Cite
|
Sign up to set email alerts
|

The Quantum Optics of Asymmetric Mirrors With Coherent Light Absorption

Abstract: The local observables of the quantised electromagnetic field near a mirror-coated interface depend strongly on the properties of the media on both sides. In macroscopic quantum electrodynamics, this fact is taken into account with the help of optical Green’s functions which correlate the position of an observer with all other spatial positions and photon frequencies. Here we present an alternative, more intuitive approach and obtain the local field observables with the help of a quantum mirror image detector m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…For the latter, we showed that it is possible to construct a mirror Hamiltonian that reproduces the classical mirror image effect for the local operators a sλ (x). This Hamiltonian was a significant find because, until that point, no locally acting mirror Hamiltonian for the EM field had been derived, and there is much interest in this topic in the literature [29][30][31][32][33]. Thus, there are certain situations in which blips provide a more physically intuitive description for modelling light-matter interactions compared to monochromatic photons.…”
Section: Local Bosonic Excitationsmentioning
confidence: 99%
“…For the latter, we showed that it is possible to construct a mirror Hamiltonian that reproduces the classical mirror image effect for the local operators a sλ (x). This Hamiltonian was a significant find because, until that point, no locally acting mirror Hamiltonian for the EM field had been derived, and there is much interest in this topic in the literature [29][30][31][32][33]. Thus, there are certain situations in which blips provide a more physically intuitive description for modelling light-matter interactions compared to monochromatic photons.…”
Section: Local Bosonic Excitationsmentioning
confidence: 99%
“…The dynamics of blips approaching the cavity walls can be described, for example, by a locally acting mirror Hamiltonian [42]. Another possibility to obtain blip operators which move along folded worldlines is to take inspiration from the mirror image method of classical electrodynamics [53][54][55] and to map the dynamics of blips onto analogous free space scenarios.…”
Section: B Optical Cavities and The Casimir Effectmentioning
confidence: 99%
“…In order to utilise the bosonic commutation relations in Eqs. (30) and (31), when analysing the dynamics of expectation values we require that the above states be pairwise orthonormal. However, under the standard inner product…”
Section: A Orthogonal Local Field Excitation Statesmentioning
confidence: 99%
“…For the latter, we showed that it is possible to construct a mirror Hamiltonian that reproduces the classical mirror image effect for the local operators a sλ (x). This Hamiltonian was a significant find because, until that point, no locally acting mirror Hamiltonian for the EM field had been derived, and there is much interest in this topic in the literature [27][28][29][30][31]. Thus, there are certain situations in which blips provide a more physically intuitive description for modelling light-matter interactions compared to monochromatic photons.…”
Section: The Connection With Hermitian Descriptions a Local Bosonic E...mentioning
confidence: 99%